2019
DOI: 10.1096/fj.201901905rr
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory role of ProBDNF in monocyte function: Implications in Stanford type‐A aortic dissection disease

Abstract: Brain-derived neurotrophic factor precursor (proBDNF) has been reported to strengthen the dysfunction of monocytes/macrophages in animal studies. However, it is still unknown the roles of proBDNF in the dysfunction of monocytes in the inflammatory diseases in humans. In the present study, we showed that proBDNF and pan neurotrophic receptor p75 were significantly upregulated in monocytes from healthy donors (HD) after lipopolysaccharide treatment. Exogenous proBDNF treatment upregulated CD40 and proinflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…Apoptosis may be triggered during early AAD stages, when intense inflammation causes severe tear of the aortic intima or when ischemia reperfusion of multi-organs stimulates release of pro-apoptotic substances, such as TNF-α and nitric oxide. Supporting this assumption, our recent study showed the serum derived from AAD patients activated gene expression of the pro-inflammatory cytokines in the cultured peripheral blood mononuclear cells from HDs ( 34 ).…”
Section: Discussionmentioning
confidence: 82%
“…Apoptosis may be triggered during early AAD stages, when intense inflammation causes severe tear of the aortic intima or when ischemia reperfusion of multi-organs stimulates release of pro-apoptotic substances, such as TNF-α and nitric oxide. Supporting this assumption, our recent study showed the serum derived from AAD patients activated gene expression of the pro-inflammatory cytokines in the cultured peripheral blood mononuclear cells from HDs ( 34 ).…”
Section: Discussionmentioning
confidence: 82%
“…ProBDNF staining was conducted as our previous study [21]. Washed cells that had been stained with above extracellular markers were fixed by fixation buffer (Invitrogen, USA, catalog: 2060489) for 20 min at room temperature and followed by permeabilization as introduced by the manufacturer protocol (Invitrogen, USA, catalog: 2009161).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Splenocytes were resuspended in DMEM supplemented with 10% heat-inactivated FBS, 2 mM glutamine, 25 mM HEPES (all from Gibco, USA), 5 × 10 −5 M 2-ME (Solarbio, China), and 100 U ml −1 penicillin. 4 × 10 5 cells were put in each well of a 96-well flat-bottom plate and stimulated with 100, 200, or 500 ng ml −1 proBDNF protein (Alomone Labs, Israel, catalog: B243) as introduced by our previous studies [21], respectively. 72 h later, splenocytes were collected and analyzed by flow cytometry as indicated above.…”
Section: Cell Culturementioning
confidence: 99%
“…We have revealed a pro-in ammatory effect of in ltrating MDMs restricted probably to between day 3 and 7 post-injury, while later resident microglia increased their conversion to an M2 phenotype that enhanced endogenous repair. Importantly, in a previous study [41] we reported an increased ratio of M1/M2-like monocytes in the peripheral circulation in patients with Stanford type-A aortic dissection (AAD), indicating that once AAD patients are subjected to the process of deep hypothermic circulatory arrest, increased numbers of M1 polarized macrophages migrate to the re-perfused spinal cord, aggravating the severity of in ammation in the micro-environment of the site of the lesion. Thus, a better understanding of the differential phenotypes of activated resident microglia and in ltrating MDMs following CNS might enable the development of novel approaches to attenuate SCIRI, for example, by timely targeting in ltrating monocytes through regulation of monocyte migration and intracellular signaling may help for the recovery.…”
Section: Discussionmentioning
confidence: 96%